Transformational Leadership Styles of the male elementary school's managers with the motivation to establish professional sport schools - Ghojan Samani, Farideh; Paktinat, Eghbal; Nekoee, Mohamad Hossein (International Journal of Education and Cognitive Sciences, 2022)
Introduction: The aim of the Present research was to study the relationship between the transformational Leadership Styles of the elementary school's managers for male and the motivation to establish specialized sport schools by them in Tehran.Materials and method: 186 among360 managers were randomly selected from nineteen educational districts in Tehran using the multistage sampling. For data collection, MLQ for transformational Leadership Styles and the researcher made questionnaire for the motivation of starting the specialized sport's schools were employed.Results: Styles can predict motivation to establish specialized sport schools. Multi regression analyses method showed that there is a significant relationship between the change transformational Leadership Styles with the motivation to start specialized sport schools in Tehran and also transformational Leadership.Conclusion: Finding also reveals that transformational Leadership Styles of managers create sense of confidence and self-reliance because they admire values and believes, furthermore they encourage the sense of prospective aspects, realization of the objectives; stimulate the sense of cooperation and attaining modern methods in performing the assignments and stimulation of motivation.